2001
DOI: 10.1099/00221287-147-9-2447
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen source governs the patterns of growth and pristinamycin production in ‘Streptomyces pristinaespiralis’

Abstract: Phosphate-limited synthetic culture media were designed to investigate the growth and the pristinamycin production of ' Streptomyces pristinaespiralis ' using different nitrogen sources. During balanced growth, either mineral or organic nitrogen sources were readily utilized. However, glutamate and alanine were used as both nitrogen and carbon source, sparing the utilization of the primary carbon source, glucose. Valine was utilized only for its nitrogen and consequently 2-ketoisovalerate was excreted in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 38 publications
3
55
0
1
Order By: Relevance
“…This phenomenon in M. echinospora may reflect the natural soil ecology of this organism, where soluble organic nitrogen compounds may also provide an energetically efficient source of carbon, necessitating only one energy-requiring uptake process. Work by Voelker and Altaba (2001) has recently demonstrated that in Streptomyces pristinaespiralis amino acids provide significant carbon to the organism. They concluded that certain amino acids (alanine and glutamine) when present in the medium 'spared' the utilization of glucose, the primary carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon in M. echinospora may reflect the natural soil ecology of this organism, where soluble organic nitrogen compounds may also provide an energetically efficient source of carbon, necessitating only one energy-requiring uptake process. Work by Voelker and Altaba (2001) has recently demonstrated that in Streptomyces pristinaespiralis amino acids provide significant carbon to the organism. They concluded that certain amino acids (alanine and glutamine) when present in the medium 'spared' the utilization of glucose, the primary carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…It is because α-amylase is an extracellular enzyme and its production is increased by its substrate [33,34]. Nitrogen sources have been reported to have an inducing effect on the production of various enzymes including al amylase [35]. The effect of different nitrogen sources (peptone, yeast extract, malt extract and beef extract) at 1 % level was determined on amylase production.…”
Section: Effect Of Various Carbon and Nitrogen Sources On Amylase Promentioning
confidence: 99%
“…These sources could sustain high antibiotic titer and this property is supposed to be linked to the slow release of nitrogenous components during the course of the fermentation. More generally, several studies have shown that nitrogen assimilation is crucial for the regulation of antibiotic production but the mechanisms involved is not clearly understood (Voelker and Altaba, 2001). …”
Section: Validation Of the Optimized Conditionmentioning
confidence: 99%